Performance Evaluation and Frequency Response Analysis of a Two Stage Two Spool Electrohydraulic Servovalve with a Linearized Model - MONDAL, Nitesh; DATTA, Biswanath (Engineering Transactions, 2019)
This article focuses on the performance study and frequency response analysis with the state space model of a linearized two stage two spool non-conventional electrohydraulic servovalve from a set of nonlinear state equations. The performance of this valve depends on many valve geometries and fluid parameters. This non-conventional electrohydraulic servovalve is controlled by a pressure controlled pilot, which generates a differential pressure between the upper and lower chambers of two spools. This differential pressure acts as the feedback element, thereby reducing the requirement for a feedback wire. In this paper, the dynamic behaviour and state-space model of the valve is established with the aid of linearized mathematical equations and the coefficients of the equations directly depend on the valves parameters, fluid properties and flow properties. The dynamic performance of this valve and the frequency response are analysed with the help of MATLAB/Simulink.